Barbados public service staff list. 1986 (Government Printing Office BridgetownBB, 1987)
Contains comprehensive list of sections and employees within the Barbados public sector for 1986. Identifies personnel in the cabinet, senate, house of assembly police and prison departments, various management boards and also provides detailed personal information eg. on office, date of birth, and dates of appointment to the Barbados service, salary scale, present grade and present department, for all other public officers. Includes lists of previous and present Governors and other government officials.
IDS